HUKUM EKONOMI PERSPEKTIF AL-QUR’AN - Djumadi Djumadi (IAIN Ambon, 2018)
The economic laws in the Qur'an through textual understanding of the word al hukm and contextually to the paragraph containing the same meaning. In addition to the word al hukm on some verses contained the term al-bātil, usurî, Tijārah, al Ba’i. The term essentially activities-activities regarding the economy. The nature of economic laws that can be understood in the form of clues Qur'an relating to the fulfillment of human needs that production is found ayākila, using the term dawala distribution, and consumption found ata term. Implimentasi Islamic economic laws need to be carried out through several approaches, among others; (a) understanding of the context of usul fiqh and fiqh rules of economics; (b) providing guidance to law enforcement in particular with regard to the decision Faraid so avoid the ruling al-bātil; (c) reasoning philosophical meaning of the Islamic economic laws still refer to the study of the Qur'an, as a primary source in Islam.